Cancer diagnosis in areas of conflict - Al-Ibraheem, Akram; Abdlkadir, Ahmed Saad; Mohamedkhair, Ali; Mikhail-Lette, Miriam; Al-Qudah, Mohammad; Paez, Diana; Mansour, Asem H. (Frontiers in Oncology, 2022)
To date, many Arab countries within the Middle East are facing political, financial, and social instability from war and conflicts. These conflicts have led to severe resources shortages and sometimes complete breakdowns in cancer care and diagnosis. Cancer diagnosis at early stages is the most vital step in achieving optimal cancer care and outcomes. Shortages in cancer diagnostic services have meant that many people within areas of conflict are ultimately deprived of these services in their own countries. Therefore, many of these cancer sufferers must bear travel expenses to neighboring countries in order to seek these services. A lack of prevention, screening, and diagnostic services for this population is known to deepen the cancer care deficit within these areas. Additionally, the financial burden of traveling abroad alongside the need to secure childcare and time off work can be overwhelming. As a result, patients within areas of conflict are frequently diagnosed at later stages and are less likely to receive optimal management plans. Though conflict-affected regions encounter many similar challenges in delivering quality cancer care, pronounced region-specific differences do exist. Therefore, it is important to build a roadmap that can provide tailored solutions to deficits in instruments, manpower, and facilities for each and every region involved. Keeping in mind the importance of collaboration and coordination on national and international levels to address the ground disparity in cancer diagnostic services, the main objective of this review article is to examine the significant problems, shortages, and difficulties in providing cancer diagnosis with a focus on imaging to conflict-affected populations in the Middle East (mainly Iraq, Syria, Yemen, and Sudan). Finally, we discuss how access to cancer diagnostic imaging services has been impacted by these conflicts.